Delta Shock Index in the Emergency Department Predicts Mortality and Need for Blood Transfusion in Trauma Patients. Issue 10 (October 2017) - Schellenberg, Morgan; Strumwasser, Aaron; Grabo, Daniel; Clark, Damon; Matsushima, Kazuhide; Inaba, Kenji; Demetriades, Demetrios
Shock Index (SI = heart rate/systolic blood pressure) predicts outcomes among trauma patients. Studies have also shown that the change in SI between the field and Emergency Department (ED) arrival (Delta SI) predicts mortality in trauma. Given the lack of reliable prehospital data, Delta SI may more accurately prognosticate if used within the ED. All trauma patients arriving to our Level I trauma center in 2014 were reviewed. Patients were matched for age, gender, mechanism of injury, and injury severity score. SI and ED Delta SI were calculated. ED Delta SI >0.1 and ≤0.1 defined the study groups. Pregnant patients, pediatric patients, and patients with incomplete data were excluded. Outcomes included intensive care unit (ICU) length of stay, blood products, and mortality. A total of 2591 patients were identified (n = 1294 patients analyzed). After matching, patients with ED Delta SI >0.1 had greater mortality (6.6 vs 2.6%, P = 0.010), need for blood transfusion (1764 vs 565 cc, P < 0.001), and ICU length of stay (5.6 vs 3.8 days, P = 0.014) compared with patients with ED Delta SI ≤0.1. In conclusion, ED Delta SI >0.1 is associated with increased mortality, need for blood transfusion, and ICU length of stay. Delta SI may be superior to traditional SI for trauma outcome prognostication.